Application of CNN based architectures in detection of distracted drivers - Arafin, Irfana; Islam, Md Mahirul; Tazwar, Syed Ittisaf; Das, Nilay Shuvra; Anika, Sabrina Tabassum (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2022.